Pemanfaatan Alat Peraga Pemanasan Global Untuk Meningkatkan Motivasi dan Pemahaman Konsep Siswa Kelas X SMAN 1 Kempo - Putra, Ardiansyah; Suswati, Lis (Universitas Nggusuwaru, 2025)
This study aims to determine the effectiveness of utilizing a simple global warming teaching aid in improving students’ motivation and conceptual understanding of global warming in Grade X. The research employed a quasi-experimental approach using a Non-Equivalent Control Group Design, involving an experimental class with 30 students and a control class with 28 students. The experimental class received learning through a simple global warming teaching aid, while the control class received conventional instruction. Research instruments consisted of a multiple-choice conceptual understanding test, a motivation questionnaire based on the ARCS model, and student activity observation sheets. The results indicate that the use of the teaching aid had a significant effect on improving students' learning outcomes. The average posttest score of the experimental class (82.7) was higher than that of the control class (74.1). The N-Gain score of the experimental class reached 0.64 (medium–high category), whereas the control class obtained 0.48 (medium category). The independent sample t-test yielded a significance value of 0.003, indicating a significant difference between both groups. Students’ motivation in the experimental class was also higher (86.5) compared to the control class (72.8), especially in the aspects of Attention, Relevance, Confidence, and Satisfaction